1975
DOI: 10.1073/pnas.72.8.2915
|View full text |Cite
|
Sign up to set email alerts
|

DNA polyintercalating drugs: DNA binding of diacridine derivatives.

Abstract: As a first step in the synthesis and the study of DNA polyintercalating drugs, dimers of acridines have been prepared. Their DNA binding properties have been studied. It has been determined that wen the chain separating the two aromatic rings is longer than a critical distance, bisintercalation is actually observed and that the DNA binding affinity becomes quite large (>108-109 M-1). It is shown also that the optical characteristics of these molecules are dependent on the sequences of DNA. The fluorescence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0
3

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(142 citation statements)
references
References 19 publications
8
131
0
3
Order By: Relevance
“…As few as one or two lesions per 3000-base-pair plasmid are sufficient for the protein-DNA complexes to bind to the nitrocellulose filter. UvrA protein, independent of the UvrB protein, binds to ditercalinium-intercalated DNA with an affinity equal to that of the UvrAB-ditercalinium-DNA or (17). The ionic strength and the pH of the UvrABC endonuclease buffer are close to those of the buffer used in the ditercalinium binding studies (10).…”
Section: Resultsmentioning
confidence: 93%
“…As few as one or two lesions per 3000-base-pair plasmid are sufficient for the protein-DNA complexes to bind to the nitrocellulose filter. UvrA protein, independent of the UvrB protein, binds to ditercalinium-intercalated DNA with an affinity equal to that of the UvrAB-ditercalinium-DNA or (17). The ionic strength and the pH of the UvrABC endonuclease buffer are close to those of the buffer used in the ditercalinium binding studies (10).…”
Section: Resultsmentioning
confidence: 93%
“…We have previously shown that the dimerization of intercalating compounds can lead to a large increase in DNAbinding affinity [22,231. The maximum binding constant expected for a dimer was here shown to be about the square of the monomer binding constant.…”
Section: Discussionmentioning
confidence: 99%
“…advantage of the fact that the fluorescence of acridine dimers depends on the DNA (A + T) content to the fourth power [22]. The dye was first preincubated with one of the DNAs for 16 h, the equilibrium was then perturbed by a large excess of the other DNA, and the exchange reaction was observed.…”
Section: Exchange Kineticsmentioning
confidence: 99%
“…Drugs containing two intercalative chromophore groups have been synthesized in recent years (Le Pecq et al, 1975;Dervan and Becker, 1978). These include bis.acridine and bis eL~idium (as well as mixed acridine-ethidium) polyintercalating agents.…”
Section: Bis Intercalation --A Probe For 8 Kinked Structural Distortimentioning
confidence: 99%
“…An important class of intercalative drugs and dyes that has received considerable attention in recent years are the bis intercalators --bifunctional intercalating agents that have two chromophore groups separated by about 10.2 A (Wakelin and Waring, 1976;Ughetto and Waring, 1977;Le Pecq et al, 1975;Butour et al, 1978;Dervan and Becker, 1978). These molecules intercalate into DNA in a neighbor exclusion mode (Le., the intercalative chromophore groups are separated.…”
Section: Bis Intercalation --A Probe For 8 Kinked Structural Distortimentioning
confidence: 99%